2021
DOI: 10.1039/d0ta11255k
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework structure–property relationships for high-performance multifunctional polymer nanocomposite applications

Abstract: Metal organic frameworks (MOFs) have emerged as a new class of crystalline nanomaterials with ultrahigh porosities and high internal surface areas. Recently, these MOFs structures with their extraordinary inherent properties...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 265 publications
0
18
0
Order By: Relevance
“…Zeolitic imidazolate (ZIF-8) metal organic frameworks have been used for highly efficient PM2.5 capture due to their excellent chemical and thermal stability. ZIF-8-modified soluble polyimide (PI) nanofibrous membranes present a high PM2.5 filtration efficiency (up to 96.6 ± 2.9%), superior thermal stability (up to 300 • C), good transmittance, excellent mechanical properties, and low pressure drop, making them a suitable candidate for PM2.5 capture, especially in harsh conditions [198,199].…”
Section: The Development Of Sustainable Facemasksmentioning
confidence: 99%
“…Zeolitic imidazolate (ZIF-8) metal organic frameworks have been used for highly efficient PM2.5 capture due to their excellent chemical and thermal stability. ZIF-8-modified soluble polyimide (PI) nanofibrous membranes present a high PM2.5 filtration efficiency (up to 96.6 ± 2.9%), superior thermal stability (up to 300 • C), good transmittance, excellent mechanical properties, and low pressure drop, making them a suitable candidate for PM2.5 capture, especially in harsh conditions [198,199].…”
Section: The Development Of Sustainable Facemasksmentioning
confidence: 99%
“…Recently, metal-organic framework composites have been extensively studied because of their novel physical and chemical properties and improved performances, which cannot be achieved by the individual parts [16][17][18]. It has been shown that by composing MOFs with suitable materials, the structure [19,20], stability [21,22], morphology [23,24], and physicochemical properties [25,26] can be signi cantly enhanced, and thus these materials provide promising applications in the areas of catalysis [27], small-molecule adsorption, storage and separation [28], batteries [29], and biomedical imaging and drug delivery [30].…”
Section: Introductionmentioning
confidence: 99%
“…9 MOFs are highly unique, and their structure can be finely tuned and designed according to the specific applications. 10 Lately, MOFs have been utilized to introduce flame retardancy to polymer matrices in nanocomposites. For example, Shi et al 11 used 3 wt % zeolitic imidazolate framework-8 (ZIF-8) MOFs to improve the limited oxygen index value of the poly(lactic acid) (PLA) reinforced MOF composites by 26%.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), which are a combination of hybrid organic–inorganic compounds with a highly porous and crystalline structure, are increasingly being used in the development of polymer nanocomposites . MOFs are highly unique, and their structure can be finely tuned and designed according to the specific applications . Lately, MOFs have been utilized to introduce flame retardancy to polymer matrices in nanocomposites.…”
Section: Introductionmentioning
confidence: 99%